2022
DOI: 10.3390/ani12202820
|View full text |Cite
|
Sign up to set email alerts
|

Dam (Canis familiaris) Welfare throughout the Peri-Parturient Period in Commercial Breeding Kennels

Abstract: Poor dam welfare throughout the peri-parturient period can also negatively affect that of their offspring. This study aimed to identify changes in physical, physiological, and behavioral metrics indicative of dam welfare throughout the peri-parturient period. Dams (n = 74) from eight U.S. Midwest commercial breeding (CB) kennels were tested at 6 and 1 week prepartum, and 4 and 8 weeks postpartum. At each time point dams underwent a stranger approach test, physical health assessment, hair collection for hair co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…The occurrence of eclampsia is higher during the first 3 weeks of lactation in small-sized dogs nursing larger litters (Pathan et al, 2011;Smith, 1986). Romaniuk et al (2022) highlighted an increased incidence of intestinal parasitosis in bitches at 4 and 8 weeks post-partum (Romaniuk et al, 2022). The percentage of dams with intestinal parasites increased from 11% and 4% at 6-and 1-week prepartum, respectively, to 23% and 15% at 4 and 8 weeks postpartum.…”
Section: Effects Of Frequent Pregnancies On the Health And Welfare Of...mentioning
confidence: 96%
See 1 more Smart Citation
“…The occurrence of eclampsia is higher during the first 3 weeks of lactation in small-sized dogs nursing larger litters (Pathan et al, 2011;Smith, 1986). Romaniuk et al (2022) highlighted an increased incidence of intestinal parasitosis in bitches at 4 and 8 weeks post-partum (Romaniuk et al, 2022). The percentage of dams with intestinal parasites increased from 11% and 4% at 6-and 1-week prepartum, respectively, to 23% and 15% at 4 and 8 weeks postpartum.…”
Section: Effects Of Frequent Pregnancies On the Health And Welfare Of...mentioning
confidence: 96%
“…Romaniuk et al. ( 2022 ) highlighted an increased incidence of intestinal parasitosis in bitches at 4 and 8 weeks post‐partum (Romaniuk et al., 2022). The percentage of dams with intestinal parasites increased from 11% and 4% at 6‐ and 1‐week prepartum, respectively, to 23% and 15% at 4 and 8 weeks postpartum.…”
Section: Judgement 2: Healthmentioning
confidence: 99%
“…For the second sample, the same patch was resampled (post-treatment) on the day the ABT was conducted, around 4-5 weeks after baseline. This sampling protocol was based on previous study that used a similar time interval between samples and found that significant difference in hair cortisol levels can be observed over a five-week period (Romaniuk et al, 2022).…”
Section: Hair Sampling For Cortisol Analysismentioning
confidence: 99%